Modified Delphi in adapting a tool to assess the level of knowledge and practice on adult enteral nutrition therapy among nurses - Weerawardhana, Piyumi L; Lalitha Meegoda MKD; Sampatha E Goonewardena (Asian Journal of Medical Sciences, 2022)
Background: Enteral nutrition (EN) is the preferred method of nutritional administration for critically ill patients according to the world’s standards. Nurses have a key role in delivering EN and assessing nurses’ knowledge and practice on this, are crucial for maintaining quality nursing care. Aims and Objectives: This study was to utilize modified Delphi in adapting a tool to assess the level of knowledge and practice on adult EN therapy among nurses in Sri Lanka. Materials and Methods: A three-round modified Delphi technique (DT) was employed in adapting a research tool to assess nurses’ knowledge and practice according to the nursing and EN guidelines in Sri Lanka. The questionnaire included 34 knowledge assessment items and 41 observational items to assess practice. Eight subject experts were purposively selected to rate each item on a 5-point Likert scale under three subheadings. Consensus defined at 80% agreement and mean ≥3. Mean value <3 was considered for suggested modifications. Experts participated in a final meeting in round 3 to finalize the tool. Results: Response rate was 100% throughout the process. During round 1, 13/34 knowledge items were modified, two were removed, and one item was added. In round 2, four items were modified, and one was removed. From the observational items, 40/41 achieved consensus, one was modified, and a new one was added in round one. One was modified in round 2. All achieved consensus by round three. The final tool contained 32 knowledge items and 42 observational items with test-retest reliability correlations ranging from 0.99 to 0.95. Conclusion: Modified DT was appropriate in achieving judgmental validity through experts’ consensus in adapting a research tool to assess nurses’ knowledge and practices on EN therapy for adult critically ill patients in Sri Lanka.